Specific knockdown of hippocampal astroglial EphB2 improves synaptic function via inhibition of D-serine secretion in APP/PS1 mice - Qi, Liang (Am J Transl Res, 2019)
Increasing evidence emphasizes the protective role of Eph receptors in synaptic function in the pathological development of Alzheimer’s disease (AD); however, their roles in the regulation of hippocampal astrocytes remain largely unknown. Here, we directly investigated the function of astroglial EphB2 on synaptic plasticity in APP/PS1 mice. Using cell isolation and transgene technologies, we first isolated hippocampal astrocytes and evaluated the expression levels of ephrinB ligands and EphB receptors. Then, we stereotaxically injected EphB2-Flox-AAV into the hippocampus of GFAP-cre/APP/PS1 mice and further evaluated hippocampal synaptic plasticity and astroglial function. Interestingly, astrocytic EphB2 expression was significantly increased in APP/PS1 mice in contrast to its expression profile in neurons. Moreover, depressing this astroglial EphB2 upregulation enhanced hippocampal synaptic plasticity, which results from harmful D-serine release. These results provide evidence of the different expression profiles and function of EphB2 between astrocytes and neurons in AD pathology.